Gambaran Pasien yang Menjalani Prosedur Bedah Emergensi di RSUP Prof. Dr. R. D. Kandou Manado Periode Januari - September 2019 - Suleman, Utrecht; Wagiu, Angelica M. J.; Tangel, Stephanus J. Ch. (Universitas Sam Ratulangi, 2020)
Abstract: Emergency surgery is performed to avoid further complications of the disease or to save the patient's life. Albeit, there are lack of data in various health centers in Indonesia regarding the evaluation of emergency surgical patients, This study was aimed to obtain the profile of patients undergoing emergency surgical procedures in the Emergency Department of Surgery at Prof. Dr. R. D. Kandou Hospital Manado from January to September 2019. This was a retrospective and descriptive study using patientsâ€™ medical records. The results showed that there were 540 patients in this study. Most of the patients were adult age group (18-59 years) as many as 343 patients (63.5%), males 366 patients (67.8%), and non-traumatic cases 436 patients (80.4%). The most common cases of trauma was epidural hemorrhage as many as 23 patients (4.3%) meanwhile the most common non-traumatic cases was chronic kidney disease as many as 122 patients (22.6%). According to the type of surgery, CDL insertion and laparotomy were performed on 131 patients each (24.3%). In conclusion, most patients undergoing emergency surgical procedures were 18-59 years old, males, and non-traumatic cases.Keywords: emergency surgery, traumatic cases, non-traumatic casesÂ Abstrak: Bedah emergensi dilakukan dalam keadaan sangat darurat untuk menghindari komplikasi lanjut dari proses penyakit atau untuk menyelamatkan jiwa pasien. Data mengenai pasien bedah emergensi di berbagai pusat kesehatan di Indonesia masih sangat kurang. Penelitian ini bertujuan untuk mendapatkan gambaran pasien yang menjalani prosedur bedah emergensi di IGD Bedah RSUP Prof. Dr. R. D. Kandou Manado periode Januari sampai September 2019. Jenis penelitian ialah deskriptif retrospektif, menggunakan data rekam medik pasien. Hasil penelitian menunjukkan bahwa dari 540 pasien, didapatkan pasien terbanyak dari golongan usia dewasa (18-59 tahun) yaitu 343 pasien (63,5%), jenis kelamin laki-laki 366 pasien (67,8%), dan kasus non-trauma 436 pasien (80,4%). Kasus trauma terbanyak yaitu epidural hemorrhage pada 23 pasien (4,3%) sedangkan kasus non trauma terbanyak chronic kidney disease pada 122 pasien (22,6%). Menurut jenis tindakan operasi yang terbanyak ialah insersi CDL dan laparotomy, masing-masing 131 pasien (24,3%). Simpulan penelitian ini ialah pasien yang menjalani prosedur bedah emergensi terbanyak ialah usia 18-59 tahun, jenis kelamin laki-laki, dan jenis kasus non-trauma.Kata kunci: bedah emergensi, kasus trauma, kasus non-trauma